The effect of external factors on industry performance: The case of Lalibela City micro and small enterprises, Ethiopia - Abriham Ebabu Engidaw (Journal of Innovation and Entrepreneurship, 2021)
The purpose of this study was to examine the effect of external factors on industry performance: in micro and small-scale enterprises. To achieve its objectives, the study employed a descriptive and explanatory research design and used quantitative research approach. The target population of the study was 395 MSEs owners working in manufacturing, trade, and service sectors. It used stratified and simple random sampling techniques and the required data have been collected from a sample size of 199 MSEs through standardized 5-point Likert-scale questionnaire. The study used both primary and secondary sources of data. For data analysis purpose, it employed descriptive and inferential statistical data analysis methods like correlation and multiple linear regression analysis. The finding of the study discovered the agreement of respondents to the positively significant relationship between external factors and industry performance in the study area. Specifically, marketing factors, financial factors, infrastructure, work premises factors, trade fair factors, and political-legal factors all have a positive effect on enterprises' performance in the study area. In addition, the study result shows that financial factors, marketing factors, infrastructure, work premises factors, and trade fair factors have a positive significant effect on industry performance but political-legal factors do not significantly affect the dependent variable industry performance. From the predicting variables, infrastructure has more effect on industry performance than the rest of variables in the study area. The study recommends that the government/micro and small enterprises development offices should maintain different supportive trainings, decrease infrastructural problems, facilitate credit services, and create attractive environment to entice or create productive MSEs. In addition, the MSEs owners should design adoptive plans and programs with the external as well as internal environment to increase their performance.
Keywords: 650; financial factors; industry performance; infrastructure factors; Marketing factors; political-legal factors; trade fair factors; work premises factors